Profitabilitas, Leverage, dan Komite Audit Pada Tax Avoidance - Hapsari Ardianti, Putu Novia (E-Jurnal Akuntansi; Vol 26 No 3 (2019)DO - 10.24843/EJA.2019.v26.i03.p13, 2019)
Tax avoidance is an action to reduce taxable income through tax planning either by following the applicable rules or not. This study aims to examine the effect of profitability, leverage, and audit committees, on tax avoidance measured using the proxy of effective tax rates (ETR) in manufacturing companies listed on the Indonesia Stock Exchange during the 2015-2017 observation period. The method of determining the sample of this study used a purposive sampling method and obtained 14 manufacturing companies. The analysis technique in this study uses multiple regression analysis techniques. Test results show that profitability and audit committees have no effect on tax avoidance. While leverage has a negative effect on tax avoidance. The theoretical implication of this research is that it can be a reference source of research relating to tax avoidance activities and can support interest theory, while practical implications are as a consideration for companies in making business decisions, especially in their tax activities Keywords: Return On Assets (ROA), Debt To Equity Ratio (DER), Audit Committee, Effective Tax Rate (ETR).